The Penguin complete Father Brown - Chesterton, G. K. (Gilbert Keith), 1874-1936. (New York : Penguin Books, 1981)
Presents forty-nine mystery stories featuring the detective talents of early twentieth-century British author G. K. Chesterton's famous character, Father Brown.
Adult
Keywords: Catholic Church -- England -- Clergy -- Fiction; Brown, Father (Fictitious character) -- Fiction; Brown, Father (Fictional character) -- Fiction; Catholic Church -- Clergy -- Fiction; Mystery fiction